Materiales de reciclaje en la enseñanza-aprendizaje de la asignatura ciencias naturales con niños de 5to año de egb de la unidad educativa comunitaria intercultural bilingüe "Inti Churi" parroquia Veintimilla, cantón Guaranda, provincia de Bolívar, durante el año 2022. - Moyano Manzano, Jomaira Estefanía (2022)
The present research work "recycling materials in the teaching learning of the natural sciences subject with children of 5th year of egb of the bilingual intercultural community educational unit "Inti Churi" veintimilla parish, canton Guaranda, province of Bolívar, during the year 2022” has the specific purpose of designing didactic material based on recycling materials that we can find in our homes, schools, the same that will allow us to build a new material to teach Natural Sciences to children in the fifth year of basic general education. The objective of this research work is to carry out this proposal of didactic resources in which students and teachers have recyclable resources to transform garbage into didactic material for the teaching-learning of Natural Sciences. The problem that originated through a diagnosis where there were teachers who taught their Natural Sciences classes in a traditional way where they did not motivate their students with tangible and didactic materials, therefore, the students lost interest in the classes. The methodology used to elaborate the proposal to create a manual where we can elaborate didactic material with recycled materials has the purpose that the students elaborate together with the teacher the materials so that they have a fun and motivating class and their teaching-learning in Natural Sciences is significant. For this, we applied research techniques that allowed us to collect information through observation sheets, surveys, interviews, with inductive-deductive methods in order to know in detail what type of materials we need for the execution of the manual. As a result, we hope that the manual for the preparation of recyclable material with teachers, students and parents will allow raising the level of interest, concentration, motivation and realizing that they should not throw away the materials we have at home, rather give them a new use didactic in order to facilitate the understanding of the students of the subject and the teacher to have an updated tool to teach their classes